La lúdica en el aprendizaje de la matemática en los estudiantes de la Escuela de Educación Básica “21 de Abril”, Riobamba - Leon Lopez, Jhoana Elizabeth (2024)
Education in general and mathematics in particular are matters of greatest importance for society. Currently, this subject has been considered a branch of knowledge that enjoys broad social prestige, due to the association made of it with scientific and technological development, which is why the present research aimed to determine the levels of curricular learning competencies, establish the recreational strategies that favor the learning of mathematics in the fifth and sixth EGB students of the “21 de Abril” School of Basic Education, period 2022-2023. The methodology used was based on a mixed approach, which allowed the collection of information; for this purpose, a questionnaire consisting of 10 specific questions related to the curricular competencies of the third cycle was applied, addressed to 166 students between fifth and sixth. EGB, and an observation sheet addressed to 7 Fifth and Sixth grade teachers of the “21 de Abril” Basic Education School. Where it was obtained as a result that the majority of fifth grade students of parallel A, B, and C and sixth grade EGB parallel A, B, C and D do not achieve the required learning. With the aforementioned, it was evident that the majority of young people have a learning deficit in mathematics, this being a serious problem since they do not reach the necessary level in the subject, causing poor academic performance, which is why it has been shown that The playful strategies applied by teachers in this context not only generate a more dynamic and participatory environment, but also have a positive impact on the understanding and retention of mathematical concepts.